Evaluating strategies to reduce greenhouse gas emissions from dairy production systems - Baker, Fern (2025)
It is important that greenhouse gas emissions (GHGe) are limited to reduce sea level rise, extreme weather events such as flooding and protect food security (GOV, 2020). The United Kingdom (UK) government have set a goal of becoming Net Zero by 2050 to limit the country’s impact on climate change (Committee on Climate Change, 2019). In 2019, agriculture accounted for 10% of UK greenhouse gas emissions, which has led to the National Farmers union (NFU) 2040 Net Zero target (NFU, 2019), who require blueprints on how to meet their set goal.